NEW BREEDING FORMS OF SOYBEAN FOR FODDER PRODUCTION - Biliavska, L. H.; Biliavskyi, Yu. V.; Diyanova, A. O.; Harbuzov, Yu. Ye. (Scientific Progress & Innovations, 2021)
Soybean is one of the promising, but insufficiently studied crops in fodder production. Its high productivi- ty, early maturity and multipurpose use (flour, green fodder, bean cake, oilseed meal, hay, silage, protein concentrates, and soybean milk) confirm the high potential in strengthening the fodder base of livestock farming. The absence of pubescence on soybean plants is an extremely rare and valuable property for the effective use of such forms in fodder production. The importance of the unique soybean parent material without pubescence for the creation of new generation varieties for various uses was highlighted. Quantitative and qualitative seed indicators are important economic and valuable traits. The following gen- erally accepted methods were used: scientific, special, laboratory and mathematical-statistical. Non-pubescent soybean lines, which have a combination of economically valuable traits and properties (high yield, large seeds, beans do not crack at ripening) were obtained by hybridization of non-pubescent forms with the best lines and varieties of Poltava selection. The qualitative composition of seed and green mass (oil, protein, fiber, ash, etc.) was analyzed in comparison with the national standards (Ustia, Yug-30, Annushka). The research results on the study of newly created, non-pubescent soybean lines, which had higher indicators of economic effectiveness than the standards had, were given. Much attention was paid to the fatty acid composition of oil in the seed of the studied varieties and lines. The results of evaluating varieties by the ratio of fatty acids were presented. This is important in order to obtain higher quality raw materials in fodder production. Thus, fifty non-pubescent lines exceeded Almaz and Adamos standard varie- ties by the indicators of economic effectiveness, in particular the fatty acid composition of oil. The peculiarities and breeding value of the newly created parent material without pubescence in selecting varieties for animal and poultry feed were determined on the basis of a detailed study of seed and green mass quality indicators of non-pubescent lines and the best varieties. Varieties without pubescence are absent in the Register of Plant Varieties of Ukraine.